104 Novel imaging techniques in skeletal dysplasias: the use of micro-ct. (4th October 2017) - Shelmerdine, S; Hutchinson, JC; Suich, J; Calder, AD; Sebire, NJ; Arthurs, OJ
Abstract : Background: We illustrate our early experience of whole body micro-CT in stillbirths and early gestation termination of pregnancies, with particular respect to skeletal dysplasias. Methods: Microfocus- computed tomography (micro-CT) is a relatively new imaging technique that provides high resolution (voxel size <100 µm 3 ), anatomic information by taking over a thousand, 2D cone-beam projections from multiple angles around a subject specimen. It is used widely in preclinical animal studies, but with few published reviews or studies regarding its use in human post-mortem imaging. In this study we demonstrate and describe the findings from our early experience of imaging perinatal skeletal dysplasias. Results: This educational exhibit will cover a range of skeletal dysplasias including osteogenesis imperfecta (types 2a and b), thanatophoric dysplasia, chondrodysplasia punctata as well as isolated limb anomalies (e.g., limb/long bone deficiencies). We focus on the imaging findings seen at micro-CT and highlight the benefits and comparisons of this technique with other imaging modalities such as post-mortem ultrasound, MRI and CT where available. Conclusion: Micro CT is a new technique being employed in post-mortem imaging of early gestation fetuses. This exhibit demonstrates the appearances of skeletal dysplasias, particularly the high resolution of bone structure achievable by this technique